1998
DOI: 10.1089/thy.1998.8.553
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Eye Muscles in Thyroid Eye Disease: Identification of the Principal Autoantigens

Abstract: Thyroid-associated ophthalmopathy (TAO) is a progressive orbital disorder associated with Graves' hyperthyroidism and, less often, Hashimoto's thyroiditis in which autoantibodies react with orbital antigens and lead to exophthalmos and eye muscle inflammation. Eye muscle (EM) membrane proteins initially reported as 55 and 64 kd are the best markers of ophthalmopathy. The "64-kd protein" is now shown to be the flavoprotein subunit of mitochondrial succinate dehydrogenase and to have a correct molecular weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…Other eye muscle autoantigens possibly involved in GO include 1) a 63-kDa calcium-binding protein, called calsequestrin, expressed in extraocular muscle and skeletal muscle, but not in the thyroid (67); 2) a 53-kDa protein, identified as another calcium-binding glycoprotein, sarcalumenin, expressed in extraocular muscle and skeletal muscle, but not in the thyroid (68); 3) a different 63-to 64-kDa protein, called 1D protein, cloned from a thyroid cDNA expression library (62), which is expressed in extraocular muscles, skeletal muscles, thyroid, testis, and other tissues (69,70); and 4) a novel eye muscle protein, called G2s, with an estimated molecular mass of about 220 kDa, expressed in extraocular muscles, skeletal muscles, and thyroid (68). A higher prevalence of circulating antibodies directed against two porcine eye muscle antigens (64-kDa and 95-kDa) has been found by immunoblotting in GO patients compared with those without eye involvement or to normal controls (71).…”
Section: Pathogenesismentioning
confidence: 99%
“…Other eye muscle autoantigens possibly involved in GO include 1) a 63-kDa calcium-binding protein, called calsequestrin, expressed in extraocular muscle and skeletal muscle, but not in the thyroid (67); 2) a 53-kDa protein, identified as another calcium-binding glycoprotein, sarcalumenin, expressed in extraocular muscle and skeletal muscle, but not in the thyroid (68); 3) a different 63-to 64-kDa protein, called 1D protein, cloned from a thyroid cDNA expression library (62), which is expressed in extraocular muscles, skeletal muscles, thyroid, testis, and other tissues (69,70); and 4) a novel eye muscle protein, called G2s, with an estimated molecular mass of about 220 kDa, expressed in extraocular muscles, skeletal muscles, and thyroid (68). A higher prevalence of circulating antibodies directed against two porcine eye muscle antigens (64-kDa and 95-kDa) has been found by immunoblotting in GO patients compared with those without eye involvement or to normal controls (71).…”
Section: Pathogenesismentioning
confidence: 99%
“…[1][2][3] Graves' patients with mild ophthalmopathy do not usually require any specific or aggressive treatment, 4 while those with moderate to severe ocular involvement need immunosuppressive or orbital surgical therapy, depending on the activity of the disease. [14][15][16][17][18][19] Moreover, quantitative magnetic resonance imaging (MRI) has been used to assess disease in eye muscle; in particular, it has been shown that T2 relaxation times are longer in oedematous than in fibrotic tissue. 8 -10 The severity of the ophthalmopathy is graded on the basis of the degree of ocular alterations, 11 whereas the activity is assessed by using the clinical activity score (CAS), 12 reflecting inflammatory changes in the periorbital tissue and the orbital adipose connective tissue, but not the involvement of the extraocular muscles (EM) in GO.…”
mentioning
confidence: 99%
“…6 A thyroid and eye-muscle shared protein has been proposed as the primary autoantigen in thyroid-associated ophthalmopathy. 5,7 The primary autoantigens in ocular MG also may differ from those in generalized MG. In ocular MG, AChR antibodies tend to be present in low titer, and were not found in one-third of a patient population studied.…”
Section: Discussionmentioning
confidence: 99%